THE INFLUENCE OF JOB EMBEDDEDNES ON EMPLOYEE PERFORMANCE WITH RESONANT LEADERSHIP AS A MODERATING VARIABLE - Muliany, Febriyan (JURNAL ILMIAH EDUNOMIKA, 2023)
ABSTRACT This research is a quantitative study with an explanatory approach. The data used in this article are primary data that researchers obtained from an online questionnaire of 350 Mitra Bangunan employees spread throughout Indonesia. The questionnaire consists of 10 statements related to Job Embeddedness, Employee Performance, and Resonant Leadership. The data obtained were analyzed using the smart PLS 4.0 analysis tool. The result in this article show convincingly that the Job Embeddedness variable can have a positive relationship direction and a significant influence on Employee Performance because the P-Values are positive and below the significance level of 0.05, namely 0.011.. In the next row, the second hypothesis can also be accepted and proven. This is due to the same reason, namely the P-Values are positive and below the significance level of 0.05, namely 0.000. On this basis, the first and second hypotheses in this article can be accepted. Keywords: Job Embeddednes, Employee Performance, Resonant Leadership